Approaches in dealing with the impact of COVID 19 pandemic: Islamic and Buddhist perspectives - Mohd Nor, Nur Suriya (2020)
Background: The COVID-19 pandemic has led to a dramatic loss of human life worldwide and presents unexpected challenges to people’s livelihood, their health, and their social lives. This pandemic has affected day to day life of thousands of peoples, who are either sick or are being killed due to the spread of this disease. Presently the impacts of COVID-19 in daily life are extensive including healthcare, economic, and social. A study on the Psychological Distress and Coronavirus Fears in the US shows that the COVID-19 pandemic is associated with high levels of psychological distress. Psychological distress is one element of overall mental health status that could be influenced by the pandemic. Other mental health conditions such as depression, anxiety, and grief could also be affected by the pandemic. In dealing with the impacts of the pandemic, both Islam and Buddhism promote several approaches such as acknowledging the fear, understanding our interconnection, accepting grief, and meditation.